Using Digital, Universal, and Intercultural Didactics to Improve Higher Education—A Project Protocol for a Norwegian Interactive and Collaborative Improvement Study Concerning Master’s Level Courses in “Theory of Science, Research Methods, and Research Ethics” - Areskoug Josefsson, Kristina; Haarr, Kjersti Helene; Eriksen, Stian Sørlie; Brossard Børhaug, Frédérique (Frontiers in Education, 2022)
Digitalization in higher education is rapidly increasing and there is a need for an increased focus on digital didactics. At the same time, there is a crucial need to focus on inclusivity in higher education to ensure equal possibilities for students to attend and complete successful higher education. The objective of this paper is to describe the protocol for the project: Digital, universal, and intercultural didactics in a master course “Theory of science, research methods and research ethics”. The project is interactive, collaborative, and uses improvement tools to test innovations to enhance digital, universal, and intercultural didactics. The follow-up research on the project´s process and outcomes will be performed with document analysis. The intention of the project is to learn through collaborative reflections and dialog, and to test digital and universal design innovations for promoting intercultural and democratic competences in higher education. When optimizing a course from the three perspectives of digital, universal and intercultural didactics, there may be conflicting perspectives or priorities that need to be resolved. Therefore, the findings from this project may provide important learning outcomes which can be of use for future pedagogical projects intending to improve digital, universal, and intercultural didactics.